Pengembangan Media Papan Pecahan Realistic Mathematic Materi Pecahan Sederhana Kelas II di SDN I Jepun Kabupaten Tulungagung - Nungki Oktaviani; Hikmah Eva Trisnantari (Jurnal Simki Postgraduate, 2024)
Learning mathematics in elementary school is very important because it presents crucial basics for further math lessons. This research is a development research aimed at producing learning media in the form of mathematical realiastic fraction boards that are valid and feasible to use. This research was conducted using the ADDIE development model. The subjects of this research were grade II students of SDN 1 Jepun. There are two data collection techniques carried out in this study, namely validity obtained through media expert validation and material expert validation by validators, validity obtained through the results of student responses to learning media. The results showed that the average value of validity, namely from material experts I getting an average value of 3.6 and material experts II getting an average value of 3.7 while in media experts I get an average value of 38 and media experts II get an average value of 37%. The feasibility of media from student learning outcomes in small groups is 67% and large groups are 92%.